Three Year Growth Performance of Acacia Crassicarpa Provenances at Serdang, Malaysia - Thepphavong, Bounhom (1997)
A trial at Universiti Putra Malaysia (UPM) Serdang, Malaysia consisting of eight provenances of A. crassicarpa Cunn. ex. Benth. was measured at three years for survival, height, diameter, tree form, specific gravity, biomass of components, volume, form factor, and leaf area. One provenance was from Irian Jaya; Indonesia, four were from Papua New Guinea, and three were from northern Queensland. All provenances survived well (>94.7 %), but they differed significantly (P<0.05) in their growth performance. Provenances from Samlleberr, Irian Jaya, Indonesia, Olive River, Queensland, Limal Malam, Papua New Guinea were found to be most promising in terms of mean height, diameter, tree form, biomass, volume, and leaf area growth. Equations to predict total biomass (both over and under bark) of eight provenances of A . crassicarpa were derived using data from 30 trees from each provenance. Regressions based on logarithmic transformations of both dependent and independent variables were found to give the best estimates of biomass components. Log Dbh was found to be a good predictor of biomass components and was used as the independent variable.